Navigating Ambiguity: Critiques of Indonesia's Health Law and its Impact on Legal Redress for Medical Malpractice Victims - Amiati, Mia; Halim, Hamzah; Hassim, Jady Zaidi (Hasanuddin Law Review, 2024)
In Indonesia, the fundamental right to health is enshrined in the 1945 Constitution, affirming every person's entitlement to live a safe and prosperous life with access to health services. The 2023 Health Law focuses on six pillars, including health security, funding, human resources, technology, primary care, and referral services, aiming to alleviate financial burdens through progressive financing. Particularly significant is the procedural change in protecting health workers, notably medical personnel, through the implementation of restorative justice methods. This article critically examines the implications of the 2023 Health Law on victim redress, particularly concerning medical personnel protection and the application of restorative justice in life-threatening medical error cases. However, the provision regarding the handling of medical personnel facing criminal allegations and disciplinary sanctions raises concerns regarding clarity and implementation. Ambiguities surrounding key terms and the prioritization of restorative justice mechanisms without clear guidelines may result in delays and inconsistencies in the legal process. This study sheds light on the need for clarity and refinement in legal frameworks to ensure the protection of both medical personnel and patients while promoting accountability and justice within the healthcare system.